Correlation between Vitamin D and Hemoglobin Levels in Anemia during Pregnancy - Sagita Darma Sari; Radiyati Umi Partan; Peby Maulina Lestari; Iche Andriyani Liberty (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Anemia in pregnancy is a serious health problem for pregnant women that can increase the risk of postpartum hemorrhage, low birth weight, and fetal growth retardation. Low intake of foods that are sources of vitamin D causes low concentrations of vitamin D (25 Hydroxyvitamin D), which can increase hepcidin expression, thereby disrupting iron hemostasis which ultimately causes anemia in pregnant women. This study aims to determine the correlation between vitamin D levels and hemoglobin in anemia in pregnancy. Methods: This study used a case-control design with 68 pregnant women as respondents. Vitamin D levels were examined using 25 (OH) D levels and the ELFA method. Data on age, body mass index (BMI), frequency of pregnancy, education, and frequency of antenatal care visits were analyzed using the chi-square test and logistic regression analysis. Results: The results of the study show that the most significant proportion occurred in the age range of 20 – 35 years (84.5%), the majority of respondents had a normal body mass index (60.3%), respondents with a pregnancy frequency of 1-3 were 86.8%, most respondents had secondary education (63.2%), respondents who had regular prenatal visits amounted to 86.8%, the majority of respondent had a vitamin d insufficiency levels (48.5%). Bivariate analysis show revealed that significant influencing factors of anemia pregnancy were age (p=0.008), BMI (p=0.040), and frequency of ANC (p=0.012). There is no correlation between hemoglobin levels and vitamin D (p=0.707). Conclusion: This study did not correlate vitamin D levels and hemoglobin levels.